A Note on Inverse Systems of S(n)-Closed Spaces - Lončar, Ivan (Sarajevo Journal of Mathematics, 2015)
The aim of this paper is to study inverse systems of the S(n)-closed spaces which are the generalization of H-closed and Urysohn-closed spaces. 2010 Mathematics Subject Classification. Primary: 54A05, Secondary: 54B35